1995
DOI: 10.1111/1523-1747.ep12317080
|View full text |Cite
|
Sign up to set email alerts
|

Human Dermal Microvascular Endothelial Cells Produce Matrix Metalloproteinases in Response to Angiogenic Factors and Migration

Abstract: Matrix metalloproteinases (MMPs) are a family of inducible enzymes that degrade extracellular matrix components, allowing cells to traverse connective tissue structures efficiently. Specific tissue inhibitors (TIMPs) function as physiologic inhibitors of MMP activity. Because neovascularization may require various proteinases, we characterized the profile of metalloenzyme production by microvascular endothelial cells (MEC) and the modulation of expression by phorbol esters (PMA) and by the physiologically rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
67
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(72 citation statements)
references
References 51 publications
5
67
0
Order By: Relevance
“…These two factors are considered the main angiogenic modulators stimulating several endothelial cell functions relevant to angiogenesis, including invasiveness and production of matrix-degrading enzymes. 10,12,28,29 While confirming the stimulatory effect of these factors on the proteolytic activity of endothelial cells, our study provides the first evidence that angiogenic factors stimulate the secretion of MMPs as membrane vesicle components.…”
Section: Discussionsupporting
confidence: 73%
“…These two factors are considered the main angiogenic modulators stimulating several endothelial cell functions relevant to angiogenesis, including invasiveness and production of matrix-degrading enzymes. 10,12,28,29 While confirming the stimulatory effect of these factors on the proteolytic activity of endothelial cells, our study provides the first evidence that angiogenic factors stimulate the secretion of MMPs as membrane vesicle components.…”
Section: Discussionsupporting
confidence: 73%
“…As expected (41)(42)(43), MMP9 activity in the supernatant of ECs alone was negligible and was not modified by the addition of IL-12 alone or in combination with Con A (Fig. 1A, lanes 4 -6).…”
Section: Il-12 Modulates Mmp9 During the Interaction Between Ecs And supporting
confidence: 81%
“…To date, several studies have demonstrated that the gelatinases, MMP-2 and MMP-9, are involved in vascular cell migration and invasion assays. [28][29] It has been documented that MMP-2 mediates the tumorassociated angiogenesis. 30,31 Microvessel density has been found to correlate with the capacity of the tumor to metastasize, and thus is considered to be one of the most important predictors of tumor progression.…”
Section: Discussionmentioning
confidence: 99%